Влијанието на технологијата врз стратегијата на претпријатијата за дистрибуција на електрична енергија - Мерџановска, Марија (Економски факултет, УКИМ, Скопје, 2013)
The doctoral dissertation explores the impact of technology over companies in times of globalization with special focus on electricity distribution companies. The dissertation seeks answers to a number of questions divided into several groups. The first group of questions refers to the possibilities for technological development in conditions of globalization. The dissertation strives to establish which are the main directions of technological development in conditions of globalization that influence the choice of business strategy. The second group of questions describes the characteristics of business strategy during globalization. The dissertation analyzes the main strategic directions, the importance of transnational companies in the transfer of technologies and the importance of correlating strategy, technology and human resources. The third set of questions is related to the environmental and technological changes that influence the strategies of electricity distribution companies. Finally, the dissertation analyzes the experience of implementing new technologies in the strategy the company for electricity distribution in Macedonia. In addition, it also researches the impact of the system for remote control over the duration of the defects and the number of defects on the three substations.
The technology impact over electricity distribution companies' strategy
Докторска дисертација одбранета во 2013 година на Економскиот факултет во Скопје, под менторство на проф. д–р Златка Поповска.
Keywords: globalization, technology development, technology paradigms, technology changes, strategy, technology and strategy, restructuring, deregulation, privatization, liberalization, electricity distribution, reengineering, effects of implementing the new technologies